2021
DOI: 10.48550/arxiv.2111.00430
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficient passive membership inference attack in federated learning

Abstract: In cross-device federated learning (FL) setting, clients such as mobiles cooperate with the server to train a global machine learning model, while maintaining their data locally. However, recent work shows that client's private information can still be disclosed to an adversary who just eavesdrops the messages exchanged between the client and the server. For example, the adversary can infer whether the client owns a specific data instance, which is called a passive membership inference attack [9]. In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Nasr et al [34] designed a white-box membership inference attack against centralized and FL by exploiting the vulnerability of stochastic gradient descent algorithm. Zari et al [57] also demonstrated the passive membership inference attack in FL. Chen et al [8] provided a generic membership inference attack to attack the deep generative models and judged whether the image belongs to the victim's training set by devising a calibration technique.…”
Section: B Membership Inference Attackmentioning
confidence: 96%
See 1 more Smart Citation
“…Nasr et al [34] designed a white-box membership inference attack against centralized and FL by exploiting the vulnerability of stochastic gradient descent algorithm. Zari et al [57] also demonstrated the passive membership inference attack in FL. Chen et al [8] provided a generic membership inference attack to attack the deep generative models and judged whether the image belongs to the victim's training set by devising a calibration technique.…”
Section: B Membership Inference Attackmentioning
confidence: 96%
“…In FL, there have been great efforts to explore its privacy leakage through various inference attacks, including membership inference [34], [57], property inference [32] and GAN [19], [50]. These inference attacks can obtain a variety of user privacy information from the local model.…”
Section: E Privacy Inference Attacks On Flmentioning
confidence: 99%
“…Attacker's Capabilities: Attackers in FL-aided energy networks possess different abilities that can be broadly divided into two types: passive and active [81]. Passive attacks are when the attacker just watches the communication between the clients and the server without messing with it.…”
Section: B Adversarial Attacks In Fl Aided Networkmentioning
confidence: 99%
“…In FL, there have been great efforts to explore its privacy leakage through various inference attacks, including membership inference [32,54], property inference [30] and GAN [18,47]. These inference attacks can obtain a variety of user privacy information from the upload model.…”
Section: Privacy Inference Attacks On Flmentioning
confidence: 99%